Promoting Health Nutrition: Strategies for Reducing Malnutrition and Improving Overall Health - Rufati, Alwaliyyunnisya; Awalia, Risky (Jurnal Perilaku Kesehatan Terpadu, 2023)
Malnutrition still poses a serious threat to world health and has far-reaching effects on both individuals and societies. The objective of this study is to objectively evaluate and assess the efficacy of various approaches used to combat hunger and promote healthy nutrition on a worldwide scale. We used a mixed-methods approach to gather quantitative and qualitative information from a variety of demographics, including kids, teens, adults, and elderly people, in order to evaluate their nutritional health and the prevalence of malnutrition. The prevalence of stunting and wasting among children under the age of five was found to be alarming, highlighting the urgent need for focused interventions to enhance child nutrition. The study also brought attention to the dual effects of malnutrition, with considerable rates of undernutrition and overnutrition seen across a range of age groups. Programs for nutrition education have been demonstrated to be helpful at raising participants' nutrition-related knowledge and encouraging healthier eating habits. Initiatives to fortify foods have shown promise in treating micronutrient deficiencies, and improvements to agriculture and food production have had a favorable influence on the variety and accessibility of food. Programs for maternal and child health made a significant contribution to the decrease in stunting and low birth weight by highlighting the value of comprehensive prenatal care in ending the cycle of malnutrition. The study emphasizes the need for context-specific and evidence-based measures to combat malnutrition and promote healthy nutrition, offering insightful information for decision-makers in healthcare and policy. We may endeavor to find lasting and fair solutions to this global health issue by utilizing effective tactics and resolving constraints. In order to enhance nutrition outcomes and general health on a larger scale, more study is needed to examine the cost-effectiveness and long-term effects of interventions.